(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
Teachers play a vital role in shaping students’ academic achievement, personal growth, and social development. Beyond delivering subject knowledge, teachers influence learners’ attitudes, values, and motivation toward learning and life. Through guidance, encouragement, and constructive feedback, teachers help students build confidence, develop critical thinking skills, and discover their individual strengths. A supportive teacher can inspire curiosity, foster resilience, and create a positive learning environment where students feel safe to express ideas and take intellectual risks. Moreover, teachers often serve as role models, demonstrating ethical behavior, responsibility, and respect, which students may carry into their future personal and professional lives. Therefore, the role of a teacher extends far beyond the classroom, contributing significantly to students’ lifelong development and success.